PENGARUH PERESEPAN ELEKTRONIK TERHADAP MUTU LAYANAN FARMASI DI RUMAH SAKIT “X” JAKARTA BARAT - Lily Widjaya (Indonesian of Health Information Management Journal (INOHIM), 2013)
AbstractIndonesia through the Ministry of Health has begun implementing Hospital Information System based computer, although it is still growing rapidly but gradually it will be done in several hospitals. One application of Hospital Information Systems including electronic prescription (e - prescription) where the doctor wrote a prescription through the data entry process is automated using software that connects at the hospital pharmacy. Hospital " X " is the new hospital . Has been in operation since December 2010 located in West Jakarta , type B with a number of 200 beds and currently has as many as 130 operational beds,  BOR in 2012 by 60 % and the average number of 400 outpatients per day. Since its establishment, the medical records of the patient has been treated using a semi- electronic paper -based medical record / manual , although it has a Hospital Information System which can be used electronically. Frequent delays in preparing the prescription and administration of medication errors to the attention of the great directors of the hospital. This research is an observational analytic cross-sectional study design. This study is a comparative quantitative study , the research aimed to compare the quality of pharmaceutical services to the adoption of electronic prescribing in order to find differences or by testing the hypothesis that the effect can be deduced about the meaning of the data obtained. Target population of this study is the entire recipe before and after implementation of an electronic prescribing in hospitals X. While the study sample is a sample that meets all inclusion criteria that had been spiked with prescription receipt and completion time of service. Through this study found that the number of samples in the implementation of electronic prescribing prescription amounted to 64 % ( 340 ) , while the number of 192 ( 36 % ) do not use electronic prescribing prescription . From the results of the estimation interval can be concluded that 95 % believed the average waiting time is between. 18.03 minutes to 21.40 minutes. Average waiting time for service of a prescription before using electronic prescriptions for 27.12 minutes . While waiting period after the application of the electronic prescription service an average of 15.53 minutes . Based on the results of the independent t-test of significance for values obtained pvalue 0.000 ( < 0.05), meaning that there is a significant difference in waiting time between the use of electronic prescribing and electronic use . Advice from research in order to conduct electronic prescription services for all outpatient services . Besides the quality of pharmacy services not only to measure the waiting time prescription services also exist other indicators such as drug administration errors that are critical to patient safety . Therefore, further research needs to be done to the influence of other factors such as quality and quantity of human resources, facilities available and the information system itself .Keywords: electronic prescribing, health information systems, medical records